The Integration of Islamic Values in Cognitive Development - Warsah, Idi; Morganna, Ruly; Warsah, Berliani Aslam Alkiromah; Warsah, Bizikrika Hably Hudaya (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
The background of this study is based on the importance of integrating moral education with academic education to create a more holistic learning environment. Islamic values such as honesty, justice, and responsibility are considered essential in the cognitive development of students. This research aims to identify and analyze how Islamic values can be integrated into students' cognitive development, as well as the normative approaches that can be used to incorporate Islamic values into the educational curriculum. The method used is a literature review by analyzing various relevant data sources. The key findings show that values such as honesty, justice, and responsibility play a crucial role in shaping students' critical and analytical thinking. Strategies like curriculum integration, thematic learning, and project-based learning (PBL) have proven effective in incorporating Islamic values into education. The results of this study support holistic education theory, which combines moral and cognitive aspects in learning. These findings make an important contribution to the existing literature and offer practical guidelines for educators and policymakers in creating a more holistic and balanced learning environment. The study has some limitations, including reliance on available literature and variability in the quality and methods of the research used. Further research is needed to explore how Islamic values can be integrated into various educational contexts and to evaluate the long-term impact of this integration on students' cognitive and moral development. Overall, the integration of Islamic values in education has the potential to yield long-term positive effects on students and the broader society.